Recurrent infected thyroglossal sinus: a unique case - Jha, Shruti; Goit, Sanjeet K.; Singh, Rakesh K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Thyroglossal sinus are a frequent clinical entity in the pediatric population, mostly present in upper midline of the neck. It is the most common complication following thyroglossal duct cysts and is well known for recurrence, if inadequately excised or infected. A careful consideration of the magnetic resonance imaging (MRI) pre-operatively helps improve the outcomes and reduces complications. We present the case of a 12-year-old boy operated four times for recurrent thyroglossal sinus. The diagnosis was confirmed by pre-operative history, physical examination as well as post-operative histopathological report of the specimen. MRI neck was used for tract diagnosis.